2010
DOI: 10.5194/angeo-28-2071-2010
|View full text |Cite
|
Sign up to set email alerts
|

Daytime sodium airglow emission measurements over Trivandrum using a scanning monochromator: first results

Abstract: Abstract. This paper presents measurement of daytime Sodium (Na) airglow emissions at 589.6 nm wavelength using a ground based 1-m scanning monochromator from Trivandrum (8.5 • N, 77 • E, 0.5 • N dip latitude), a nearequatorial station in India. The Na emission intensity exhibits significant temporal variability within a day and from one day to another. The Na intensity has been compared with the daytime OH airglow intensity at 731.6 nm simultaneously measured using the unique Multiwavelength Dayglow Photomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…These two lines were not matching with excitation of any of the elements such as Fe, O or H which are present inside the plasma. Since sodium doublet (Na D) lines have been well identified [12][13][14][15], but never reported for hydrogen plasma, further experiments with a low pressure sodium vapour lamp (LPSVL) was carried out. In this experiment emissions from both LPSVL and plasma were simultaneously captured by two channels of multi channel Czerny Turner spectrograph.…”
Section: Resultsmentioning
confidence: 99%
“…These two lines were not matching with excitation of any of the elements such as Fe, O or H which are present inside the plasma. Since sodium doublet (Na D) lines have been well identified [12][13][14][15], but never reported for hydrogen plasma, further experiments with a low pressure sodium vapour lamp (LPSVL) was carried out. In this experiment emissions from both LPSVL and plasma were simultaneously captured by two channels of multi channel Czerny Turner spectrograph.…”
Section: Resultsmentioning
confidence: 99%
“…D 1 line (5,896 Å) is chosen for the present study. Near the bottom of this absorption line, Na emission feature is noticed (Hossain et al 2010). The system is then tuned to the wavelength position of this emission feature, and the temporal variation of Na airglow intensity is measured during daytime.…”
Section: Methodsmentioning
confidence: 99%
“…They also have found through the Na airglow VER estimation using the contribution from the mesospheric ozone and temperature data that the peak emission altitude does not match the altitude of the maximum correlation between the Na atoms and the Na airglow, and hence suggested that the altitude variation of the pressure-dependent collisional quenching needs to be considered, on this occasion, to account for the observed Na airglow intensity variation. In a recent paper, Hossain et al (2010) has reported that daytime Na airglow exhibits significant variability within a day and from one day to another. Also, it has been shown that the dynamics and the chemistry affect its temporal variation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations